Prediagnosis Body Mass Index, Physical Activity, and Mortality in Endometrial Cancer Patients - Arem, Hannah; Park, Yikyung; Pelser, Colleen; Ballard-Barbash, Rachel; Irwin, Melinda L.; Hollenbeck, Albert; Gierach, Gretchen L.; Brinton, Louise A.; Pfeiffer, Ruth M.; Matthews, Charles E. (JNCI : Journal of the National Cancer Institute, 2013)
Background Higher body mass index (BMI) and inactivity have been associated with a higher risk of developing endometrial cancer, but the impact on endometrial cancer survival is unclear. Methods Among incident endometrial cancer case subjects in the National Institutes of Health-AARP Diet and Health Study, we examined associations of prediagnosis BMI (n = 1400) and physical activity (n = 875) with overall and disease-specific 5- and 10-year mortality. Using Cox proportional hazards regression, we estimated hazard ratios (HRs) and 95% confidence intervals (CIs), adjusting for tumor characteristics, treatment, and other risk factors. All statistical tests were two-sided. Results Compared with women with a BMI in the range of 18.5 to less than 25kg/m(2), the hazard ratios for 5-year all-cause mortality were 1.74 (95% CI = 1.13 to 2.66) for BMI in the range of 25 to less than 30kg/m(2), 1.84 (95% CI = 1.17 to 2.88) for BMI in the range of 30 to less than 35kg/m(2), and 2.35 (95% CI = 1.48 to 3.73) for BMI greater than or equal to 35kg/m(2) (P trend < .001). Higher BMI was also statistically significantly associated with poorer endometrial cancer-specific but not cardiovascular disease 5-year mortality. Hazard ratio estimates for 10-year all-cause and endometrial cancer-specific mortality as related to BMI were similar to 5-year hazard ratio estimates, whereas 10-year cardiovascular disease mortality became statistically significant (HR = 4.08; 95% CI = 1.56 to 10.71 comparing extreme BMI groups). More physical activity was related to lower all-cause 5-year mortality (HR = 0.57, 95% CI = 0.33 to 0.98 for >7 hours/week vs never/rarely), but the association was attenuated after adjustment for BMI (HR = 0.64, 95% CI = 0.37 to 1.12). No association was observed between physical activity and disease-specific mortality. Conclusions Our findings suggest that higher prediagnosis BMI increases risk of overall and disease-specific mortality among women diagnosed with endometrial cancer, whereas physical activity lowers risk. Intervention studies of the effect of these modifiable lifestyle factors on mortality are needed.